An organizational perspective of values - Geremias Leal, Fernanda; Barreto Moraes, Mário César (Revista de Negócios, 2016)
The studies on organizational values have acquired centrality in the Business Administration field within a functionalist perspective, based on the evidence that organizations with strong cultures achieve better global results. The belief in the potentiality of this resource, especially in regard to behavior alignment aimed for goal achievement, has prompted the quest for a theoretical structure of the concept and development of different ways of assessment. More contemporary perspectives, however, have come across significant constraints within the existing framework, especially the ones that disregard the dynamics of this concept. Such views provoke debates about the practical capacity of the instruments used for assessing the basis of values that govern organizations. The present study seeks to present a contemporary theoretical review on organizational values. Methodologically, it is a qualitative study that brings back to light the theory of value and its applicability to the organizational sphere, based on a survey of a literature review of empirical articles published on the subject between the period of 2000 and 2016.